2007
DOI: 10.1889/1.2785299
|View full text |Cite
|
Sign up to set email alerts
|

P‐39: Perceptual Tests of the Temporal Response of a Shuttered LCoS Projector

Abstract: Perceptual motion blur was studied using imagery presented on an LCoS projector equipped with a mechanical shutter to reduce pixel hold-time. Perceptual measures of image blur were obtained with a simple test stimulus, as well as imagery similar to that used in Air Force flight simulation and training. Measured pixel hold-time was found to accurately predict perceived blur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…The blur at 120fps frame rate is much reduced comparing to that of 60fps, and further reduction is confirmed at 240fps frame rate. The results of 240fps on Figure 8 are same degree of the previous study for a shuttered 60fps LCOS with 25% hold time [3]. It is clear that a high frame rate is very effective for reducing perceived blur.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The blur at 120fps frame rate is much reduced comparing to that of 60fps, and further reduction is confirmed at 240fps frame rate. The results of 240fps on Figure 8 are same degree of the previous study for a shuttered 60fps LCOS with 25% hold time [3]. It is clear that a high frame rate is very effective for reducing perceived blur.…”
Section: Discussionsupporting
confidence: 78%
“…Previous report has indicated that the mechanical shutter is a quite effective way to reduce perceived blur in LCOS projectors [3]. A 60fps LCOS projector equipped with a mechanical shutter, which reduced the pixel hold-time by approximately 25%, resulted in a significant reduction in perceived blur, offering a performance similar to a 60fps CRT projector.…”
Section: Introductionmentioning
confidence: 94%
“…Six observers participated in this experiment, which was a simplified application of the moving-line test that we have previously described [12]. In the modified procedure used to evaluate the GxL projector, observers tracked a pair of white, 20 pixel wide bars with a 1-pixel gap between the bars against a black background and reported if the gap was detectable.…”
Section: Tracking Blurmentioning
confidence: 99%
“…However, tracking blur, which occurs when an observer tracks moving imagery, is greater for most digital projectors due to a longer within-frame hold-time than that of CRTs [6,7]. Digital projectors can be relatively easily modified to reduce their holdtime, and we have previously evaluated several such projectors for possible use in flight-simulator applications [12,13]. Those evaluations verified the high contrast and spatial resolution of digital projectors, and also indicated that tracking blur could be reduced sufficiently for use in many simulator applications.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been studied in ref. [6] for the specific case of flight simulators. The conclusion was that displays with hold times between 6 to 8msec (at half amplitude) might be adequate for most situations, and that 4msec would be needed for the most demanding applications like fast-jet flight simulation.…”
Section: Smearing Reductionmentioning
confidence: 99%